Spatial modeling to identify potential areas for the generation of diffuse pollution in the Cotia River Basin - SP - Toniolo, Bruno Pereira [UNESP]; Nery, Liliane Moreira [UNESP]; da Cunha e Silva, Darllan Collins [UNESP] (FapUNIFESP (SciELO), 2024)
The scarcity of data on diffuse pollution in Brazilian hydrographic basins makes it difficult to create models that allow the assessment of the generation of polluting sources. Thus, this work aimed to simplify the identification of imminently polluting regions, applying two methods: the Non-Point Potential Index (PNPI) and the Mathematical Model of Correlation Land Use and Water Quality (MQUAL). These two models were developed in Geographic Information System (GIS) analyzing Contribution Areas (CAs) in the Cotia River Basin (SP). The average PNPI of the basin was classified as low potential for diffuse pollution, however, areas of high potential increased especially on the banks of the Cotia River. The MQUAL indicated a significant daily input of pollutants: approximately 10 kg of Total Phosphorus (PT), 200 kg of Total Nitrogen (NT) and 8 tons of Total Suspended Solids (TSS). The land uses and occupations that contribute most to diffuse pollution are urban area and industry, so the sectoral analysis of the watershed allowed to categorize areas of greater potential diffuse pollution, a useful tool for understanding the effects of anthropization on water resources.
Modelagem espacial para identificação de áreas potenciais à geração de poluição difusa na Bacia Hidrográfica do Rio Cotia - SP
Keywords: Diffuse pollution; Geoprocessing; Water resources